2019
DOI: 10.1002/ccr3.2072
|View full text |Cite
|
Sign up to set email alerts
|

A case of palisaded neutrophilic granulomatous dermatitis with subsequent development of chronic myelomonocytic leukemia

Abstract: Key Clinical Message Palisaded neutrophilic granulomatous dermatitis is a cutaneous marker of a systemic disease. Clinicians’ goal should be directed toward determining an underlying condition. Even if the initial investigation is inconclusive, it may be necessary that some tests are repeated, since a serious underlying disease could be revealed in the course of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
3
12
0
3
Order By: Relevance
“…On review of the literature, there have been 4 previous reports of PNGD occurring in the context of CMML. 3 Our case is noteworthy because it has a striking similarity to 3 patients described in detail by Federman et al 2017 in which a diagnosis of PNGD preceded identification of underlying CMML. All patients in that series presented with a widespread erythematous to brown papular eruption involving the trunk and extremities.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…On review of the literature, there have been 4 previous reports of PNGD occurring in the context of CMML. 3 Our case is noteworthy because it has a striking similarity to 3 patients described in detail by Federman et al 2017 in which a diagnosis of PNGD preceded identification of underlying CMML. All patients in that series presented with a widespread erythematous to brown papular eruption involving the trunk and extremities.…”
Section: Discussionsupporting
confidence: 77%
“…The association between PNGD and hematologic malignancies, particularly chronic myelomonocytic leukemia (CMML), is rare with only a few scattered reports in the literature. 2,3 CMML is a malignant hematopoietic disorder with features of a myeloproliferative neoplasm and myelodysplastic syndrome. 4 Peripheral blood monocytosis and bone marrow dysplasia characterize this form of leukemia, which may also be accompanied by cytopenias and splenomegaly.…”
Section: Introductionmentioning
confidence: 99%
“…PNGD was first discovered in patients with rheumatoid arthritis and hence primarily named rheumatoid papules and IGD with cutaneous cords and arthritis. 1 Subsequently, more clinicians observed similar features in other autoimmune conditions such as pediatric sarcoidosis, 4 Takayasu arteritis, 2 systemic lupus erythematosus, and EGPA.…”
Section: Discussionmentioning
confidence: 94%
“… 5 Recent studies have shown that different biopsies from multiple lesions within one patient with PNGD may present distinctively under the microscope. 2 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation